Cultural differentiated time perception in consumption experience - ZHOU, JING (2016)
This paper is to investigate the temporal perception between China and British and its influence on their consumption behavior regard to technological products. A qualitative interview was adopted here for the research. Twenty in-depth interviews were conducted to seek the difference and similarity of temporal perception between two cultures. Also their time perceptive that related technological products consumption behavior. The findings from study show that China and British share a similar time perspectives. Participants from those two countries had strong present and future orientation. Further, the findings support that time play a special role in consumer behavior and it have impacts on technological products option. The findings also show that brand loyalty and inter-brand connection can save customer time and stimulate the consumption of technological products to a certain degree.